FACTORS INFLUENCING STUDENT SATISFACTION WITH THE MENU OF THE FREE NUTRITIOUS MEAL PROGRAM (MBG) AT UPT SMP NEGERI 4 PANCARIJANG - Mutiara Sani Irwan; Pratiwi Ramlan; Devy Febrianti; Mardhatillah (JTH: Journal of Technology and Health, 2026)
The Free Nutritious Meal Program (MBG) is a government intervention aimed at fulfilling the nutritional needs of school-age children. However, its success is not solely determined by nutritional adequacy, but also by student satisfaction as direct beneficiaries. This study aimed to analyze factors influencing student satisfaction with the MBG menu at UPT SMP Negeri 4 Pancarijang. A quantitative approach with cross-sectional design was employed. The population consisted of 181 students participating in the MBG program. Using Slovin's formula, 125 students were selected through stratified random sampling. Data were collected via questionnaire measuring knowledge, attitude, menu perception, and teacher support as independent variables, and student satisfaction as the dependent variable. Multiple linear regression was used for data analysis. Results showed that attitude (p = 0.033) and menu perception (p = 0.000) significantly influenced student satisfaction, while knowledge (p = 0.855) and teacher support (p = 0.131) did not show significant effects after controlling for other variables. Simultaneously, all four variables significantly influenced satisfaction (p = 0.000), explaining 59.4% of the variation in student satisfaction. Menu perception was the most dominant variable, emphasizing that improvement of menu quality in terms of taste, variety, and appearance is the primary priority for enhancing student satisfaction with the MBG program.